Glandular Trichomes and Essential Oils Variability in Species of the Genus Phlomis L.: A Review - Irina Neta Gostin; Cristian Felix Blidar (Plants, 2024)
The genus Phlomis is one of the largest genera in the Lamiaceae family and includes species used since ancient times in traditional medicine, as flavoring for food and as fragrance in cosmetics. The secretory structures (represented by glandular trichomes) as well as the essential oils produced by them constitute the subject of this review. While representatives of this genus are not typically regarded as large producers of essential oils compared to other species of the Lamiaceae family, the components identified in their essential oils and their biological properties necessitate more investigation of this genus. A comprehensive analysis of the specialized literature was conducted for each of the 93 currently accepted species to identify all the results obtained by researchers regarding the secretory structures and essential oils of this genus up to the present time. Glandular trichomes, still insufficiently studied, present morphological peculiarities that differentiate this genus within the family: they are of two categories: capitate (with a wide distribution in this genus) and dendroid. The peltate trichomes, characteristic of many species of this family, are absent. The essential oils from the species of the genus Phlomis have been much more widely studied than the secretory structures. They show considerable variability depending on the species and the environmental conditions.